2010
DOI: 10.1093/forestry/cpq018
|View full text |Cite
|
Sign up to set email alerts
|

A participatory process for identifying and prioritizing policy-relevant research questions in natural resource management: a case study from the UK forestry sector

Abstract: There is growing interest in widening public participation in research and practice in environmental decision making and an awareness of the importance of framing research questions that reflect the needs of policy and practice. The Top Ten Questions for Forestry (T10Q) project was undertaken in 2008 to investigate a process for compiling and prioritizing a meaningful set of research questions, which were considered by participating stakeholders to have high policy relevance, using a collaborative bottom-up ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…According to a recent participatory process, 'finding the most technically and financially effective ways of identifying, monitoring and controlling invasive species, pests and disease' is one of the top policy-relevant research questions in the UK forestry sector (Petrokofsky et al 2010). This aim is complicated by concurrent objectives in biodiversity conservation.…”
Section: Interdisciplinarity Stakeholder Involvement and Trade-offsmentioning
confidence: 99%
“…According to a recent participatory process, 'finding the most technically and financially effective ways of identifying, monitoring and controlling invasive species, pests and disease' is one of the top policy-relevant research questions in the UK forestry sector (Petrokofsky et al 2010). This aim is complicated by concurrent objectives in biodiversity conservation.…”
Section: Interdisciplinarity Stakeholder Involvement and Trade-offsmentioning
confidence: 99%
“…In the past decade a number of similar initiatives have been conducted globally (Parsons et al 2014, Sutherland et al 2009) and regionally in the United States , Canada , the Alps (Walzer et al 2013) and in Switzerland (Braunisch et al 2012). In addition to these ranking exercises, thematic and sectoral research priorities have been identified in the fields of forest management (Petrokofsky et al 2010), agriculture (Pretty et al 2010), invasive species (Matzek et al 2013) and paleo-ecology (Seddon et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Decision making and public opinion appears as one of the relevant themes for future research in natural resource management (Petrokofsky et al, 2010). In practice, MCDM methods have been implemented to inform decision problems and public participation and they will continue to be essential in forest and environmental management (Kangas and Kangas, 2005).…”
mentioning
confidence: 99%